HIV Prevention Services and Testing Utilization Behaviors among Men Who Have Sex with Men at Elevated Risk for HIV in Chongqing, China. (25th March 2014) - Huang, Dayong; Hu, Yifei; Wu, Guohui; Jia, Yujiang; Lu, Rongrong; Xiao, Yan; Raymond, H. F.; McFarland, Willi; Ruan, Yuhua; Ma, Wei; Sun, Jiangping
Abstract : Objective . To investigate barriers and correlates of the use of HIV prevention services and HIV testing behaviors among men who have sex with men in Chongqing. Methods . Three consecutive cross-sectional surveys provided demographic, sexual behavior, HIV/syphilis infection, HIV prevention service, and testing behavior data. Results . Of 1239 participants, 15.4% were infected with HIV, incidence was 12.3 per 100 persons/year (95% CI: 9.2–15.3), 38% of the participants reported ever having unprotected insertive anal sex, 40% ever received free condom/lubricants in the past year, and 27.7% ever obtained free sexually transmitted infection examination/treatment in the past year. Multivariable logistic regression revealed that lower levels of HIV/AIDS related stigmatizing/discriminatory attitudes, full-time jobs, and sex debut with men at a younger age were independently associated with use of free condom/lubricants. Large social networks, higher incomes, and sexual debut with men at a younger age were associated with use of any HIV prevention and HIV testing services. Lower levels of stigmatizing/discriminatory attitudes were also associated with HIV testing. Fearing needles and being unaware of the venues for testing were top barriers for testing service utilization. Conclusion . It is imperative to address HIV/AIDS related stigmatizing/discriminatory attitudes and other barriers while delivering intervention and testing services.